Analysis of Chromosomal Aberrations and Micronuclei in Type 2 Diabetes Mellitus Patients - Pappuswamy, Manikantan; Rajesh, Nanditha; Maria Philip, Aaggi (Asian Pacific Journal of Cancer Biology, 2020)
Introduction: Type 2 diabetes mellitus is a metabolic disorder characterized by insulin resistance and disrupted insulin secretion. It is often linked to injuries, malfunction and failure of several organs in the long term. The elevated chromosomal disruptions and genetic complications in diabetic patients are due to the increased production of reactive oxygen species. Materials and Methods: The current study used chromosomal aberration assay and micronucleus assay to analyze the extent of abnormalities in the subjects. Results: The results showed increase in frequency of chromosomal aberrations in diabetic patients when compared to the control group (2.76±1.65 and 0.47±0.75 respectively). They also showed higher levels of micronuclei formation than the control participants (13.28±8.63 and 4.12±8.89 respectively).The correlation analysis indicated positive relationship between total aberrations and duration of diabetes. Conclusion: These results indicate that diabetes is associated with genomic instability and studies at a genetic level can be employed for early detection.